Chondroprotective Activity of Murraya exotica through Inhibiting β-Catenin Signaling Pathway. (19th December 2013) - Wu, Longhuo; Liu, Haiqing; Zhang, Rui; Li, Linfu; Li, Jialin; Hu, Haibo; Huang, Hao
Abstract : Osteoarthritis (OA) is a degenerative joint disease that affects millions of people. Currently, there is no effective drug treatment for it. The purpose of this study is to investigate the chondroprotective effects of Murraya exotica (L.) on OA. The rat OA models were duplicated to prepare for separating OA chondrocytes, synovial fluid (SF), and serum containing M. exotica (50 mg/kg, 100 mg/kg, and 200 mg/kg), M. exotica showed the activity of decreasing the contents of TNF- α and IL-1 β in SF and the chondrocyte apoptosis in a dose-dependent manner. To investigate the probable mechanism, quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting were used to determine gene expression and protein profiles, respectively. The results reveal that M. exotica can downregulate mRNA and protein expressions of β -catenin and COX-2 and reporter activity significantly. Conclusively, M. exotica exhibits antiapoptotic chondroprotective activity probably through inhibiting β -catenin signaling.